Dropped on the way to the top: Gender and managerial derailment. Issue 4 (21st October 2016) - Bono, Joyce E.; Braddy, Phillip W.; Liu, Yihao; Gilbert, Elisabeth K.; Fleenor, John W.; Quast, Louis N.; Center, Bruce A.
Abstract: We attempt to make sense of ongoing gender disparities in the upper ranks of organizations by examining gender bias in leaders' assessments of managers' derailment potential. In a large managerial sample (Study 1: N ∼ 12, 500), we found that ineffective interpersonal behaviors were slightly less frequent among female managers but slightly more damaging to women than men when present. Evidence of bias was not found in performance evaluations but emerged when leaders were asked about derailment potential in the future. We replicated this pattern of effects in a second large managerial sample (Study 2: N ∼ 35, 500) and in two experimental studies (Studies 3 and 4) in which gender and interpersonal behaviors were manipulated. In Study 4, we also showed that when supervisors believe that a manager might derail in the future, they tend to withdraw mentoring support and sponsorship, which are especially critical for women's career advancement. Our research highlights the importance of leaders' perceptions of derailment potential—which differ from evaluations of performance or promotability—both because they appear to be subject to stereotype‐based gender bias and because they have important implications for the mentoring and sponsorship that male and female managers receive.